3+3(2-6)squared=

Simple and best practice solution for 3+3(2-6)squared= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+3(2-6)squared= equation:


Simplifying
3 + 3(2 + -6) * squared = 0

Combine like terms: 2 + -6 = -4
3 + 3(-4) * squared = 0

Multiply 3 * -4
3 + -12adeqrsu = 0

Solving
3 + -12adeqrsu = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -12adeqrsu = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -12adeqrsu = 0 + -3
-12adeqrsu = 0 + -3

Combine like terms: 0 + -3 = -3
-12adeqrsu = -3

Divide each side by '-12deqrsu'.
a = 0.25d-1e-1q-1r-1s-1u-1

Simplifying
a = 0.25d-1e-1q-1r-1s-1u-1

See similar equations:

| -8a-2a=-10 | | b+4=2b-3 | | -x-8=x+2 | | -4(5x-4)+3(4x+2)= | | 6n-3=3n-15 | | 2(2x+2)-3(x-4)= | | A/2=36 | | 84=78+n | | -x+7x=-12 | | -x^2+5=(4x-1)(4x-1) | | 4a+7a=7a+16 | | v/-4=13 | | -0.25+0.6= | | -0.25-0.6= | | (13m-11)=2m+5 | | -6(b-6)+4=88 | | 4.5s-s= | | 0.25-0.6= | | x*3+75=x*9-9 | | 18x11/(18x11)= | | 13m-11=2m+5 | | 2v-1=11 | | 63=2(6x-1)+5 | | 16a-5a= | | d+d+3d= | | -66=6(1+4m) | | 8(4n+2)=240 | | -3(2x-4)+(5x-3)= | | 11h+h= | | 3M-2p=0 | | 6-p^2=47 | | -(4x+6)-3(3x+6)= |

Equations solver categories